Relationship Between Total Prothrombin, Native Prothrombin and the International Normalized Ratio (INR) - Braun, P J; Szewczyk, K M (Thrombosis and Haemostasis, 1992)
Plasma levels of total prothrombin and fully-carboxylated (native) prothrombin were compared with results of prothrombin time (PT) assays for patients undergoing oral anticoagulant therapy. Mean concentrations of total and native prothrombin in non-anticoagulated patients were 119 ± 13 µg/ml and 118 ± 22 µg/ml, respectively. In anticoagulated patients, INR values ranged as high as 9, and levels of total prothrombin and native prothrombin decreased with increasing INR to minimum values of 40 µg/ml and 5 µg/ml, respectively. Des-carboxy-prothrombin increased with INR, to a maximum of 60 µg/ml. The strongest correlation was observed between native prothrombin and the reciprocal of the INR (1/INR) (r = 0.89, slope = 122 µg/ml, n = 200). These results indicated that native prothrombin varied over a wider range and was more closely related to INR values than either total or des-carboxy-prothrombin. Levels of native prothrombin were decreased 2-fold from normal levels at INR = 2, indicating that the native prothrombin antigen assay may be a sensitive method for monitoring low-dose oral anticoagulant therapy. The inverse relationship between concentration of native prothrombin and INR may help in identification of appropriate therapeutic ranges for oral anticoagulant therapy.